Calculation of excited states of the polycation Bi 3+ 5 by the spin-orbit configuration interaction method - Romanov, A.N.; Kondakova, O.A.; Sulimov, A.V.; Sulimov, V.B.; Vtyurina, D.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
The polycation Bi 3+5 is one of the possible emitters of the broadband NIR luminescence from optics materials doped by bismuth. The Bi 3+5 lowest excited states are calculated by the spin-orbit configuration interaction method. These excited states are responsible for the optical absorption features in NIR, visible and near UV spectral ranges. The numerical results are in good agreement with the experimental data corresponding to the Bi 3+5 absorption spectrum in chloroaluminate melts. The existence of the lowest excited state with radiative transition to the ground state in NIR is confirmed. Thus, the Bi 3+5 polycation can be a source of the broadband NIR emission in bismuth doped optical materials.